2017
DOI: 10.1007/s40618-017-0676-0
|View full text |Cite
|
Sign up to set email alerts
|

Transoral thyroidectomy: advantages and limitations

Abstract: In this opinion paper of the Journal of Endocrinological Investigation, leading experts in the field report on their current clinical experience with a novel approach for thyroid gland surgery, namely, "transoral thyroidectomy" (TOT). This feasible and novel surgical procedure does not require visible incisions and is, therefore, a truly scarless surgery. Patients meeting the following criteria can be considered as candidates for TOT: (a) an ultrasonographically (US) estimated thyroid diameter ≤10 cm; (b) US-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 34 publications
0
48
0
9
Order By: Relevance
“…The transoral approach is the most minimally invasive surgery through the closest access, and it is the most cosmetically perfect with real scarless operation among remote access surgeries. The midline approach facilitates total thyroidectomy easily with excellent access to both entire lobes and provides an operative view with the craniocaudal approach, which facilitates CCND completely . The purpose of this study is to report the early experiences of transoral robotic thyroidectomy (TORT) and compare it with the existing BABA method.…”
Section: Introductionmentioning
confidence: 99%
“…The transoral approach is the most minimally invasive surgery through the closest access, and it is the most cosmetically perfect with real scarless operation among remote access surgeries. The midline approach facilitates total thyroidectomy easily with excellent access to both entire lobes and provides an operative view with the craniocaudal approach, which facilitates CCND completely . The purpose of this study is to report the early experiences of transoral robotic thyroidectomy (TORT) and compare it with the existing BABA method.…”
Section: Introductionmentioning
confidence: 99%
“…define a maximum allowable thyroid diameter as 10 cm, while Wang et al . utilize an 8-cm maximum thyroid diameter value in addition to a 2-cm maximum nodule size (22,28,38,39). Dionigi et al .…”
Section: Indications and Inclusion Criteriamentioning
confidence: 99%
“…Dionigi et al . additionally limit the size of the dominant nodule to no larger than 5 cm, and the total thyroid volume to no more than 45 mL as per preoperative ultrasonography (28). Other authors have used only maximum diameter of the tumor/nodule as a size indication, with Yang et al .…”
Section: Indications and Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, TONS provides excellent visualization of the bilateral RLN’s near their insertion into the larynx. This view is familiar to most experienced endocrine surgeons, and provides a favorable angle of dissection along the plane of the nerve (Figure 3), and allows for optimal visualization when transposing the nerve on the right, thus facilitating a true comprehensive CND (1926,34,35,37). Finally, we have found that there is enhanced visualization and magnification of the parathyroid glands with TONS, aiding in their preservations and prevention of hypoparathyroidism, which is of particular concern, given the reported incidence of temporary hypoparathyroidism of 14–40% after CND (3840).…”
Section: Technical Advantagesmentioning
confidence: 99%